2006
DOI: 10.1149/1.2189971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Composition on Adhesion of Directly Electrodeposited Copper Film on TiN

Abstract: Copper citrate ͑Cu-Cit͒ baths are effective mediums for seedless electrochemical deposition ͑ECD͒ of copper with strong adhesion property on TiN. The chemical equilibrium diagrams of chemical fraction vs pH were used to explain the cause of good adhesion of copper deposits on TiN. The kind and the amount of Cu-Cit complexes in a bath were determined according to pH and the concentration ratio of copper and citrate, ͓Cu 2+ ͔/͓Cit −3 ͔. It was found that CuCit − among various Cu-Cit complexes participated in adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…Since electrodeposition is significantly affected by the nature of the organometallic complex, 31,[40][41][42][43][44] it was first necessary to determine the nature of the complex formed by Cu ions and citrate. It has been reported that the complex formed between Cu ions and citrate is dependent on the pH of the electrolyte and the concentration ratio between Cu ions and citrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since electrodeposition is significantly affected by the nature of the organometallic complex, 31,[40][41][42][43][44] it was first necessary to determine the nature of the complex formed by Cu ions and citrate. It has been reported that the complex formed between Cu ions and citrate is dependent on the pH of the electrolyte and the concentration ratio between Cu ions and citrate.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the complex formed between Cu ions and citrate is dependent on the pH of the electrolyte and the concentration ratio between Cu ions and citrate. [40][41][42][43][44] For pH < 2, no complex was observed as the citric acid largely favored its neutral, non-dissociated form. However, once pH>2, citric acid dissociated to H 2 45 Complex formation can be ob- served through UV-vis spectroscopy, with absorption at 800 nm being associated with hydrated, non-complexed Cu ions, and a blueshift and intensity increase being associated with complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al reported that in the pH = 5.8 − 6.5 interval, depending on Cu concentration, (Cu 2 Cit 2 (OH) 2 ) 4− is reported to be the most stable complex species in solution and it suppresses the direct reduction of Cu from the electrolyte [28].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, Cu 2 (Cit) 2 OH 3− was useful to electrodeposit a very thin, uniform Cu film, and CuCit − was effective in promoting interfacial adhesion between Cu electrodeposits and TiN diffusion barrier layer. 34 Thus, it is expected that the dominant formation of CuCit − and Cu 2 (Cit) 2 OH 3− may also be helpful in electrodepositing Cu thin films directly on Ti diffusion barrier layer. Figure 2 shows a CV curve plotted in the cathodic potential region up to −2.0 V in the Cu-Cit electrolyte of pH 3.40.…”
Section: Resultsmentioning
confidence: 99%